1998
DOI: 10.1103/physrevb.57.5163
|View full text |Cite
|
Sign up to set email alerts
|

Photoexpansion inAs2S3glass

Abstract: Mechanisms of photoexpansion in chalcogenide glasses have been studied in three respects. A detailed x-ray investigation of As 2 S 3 shows that the photoexpansion can be connected with asymmetric broadening of the first sharp diffraction peak. Comparison between radiation-induced volume changes and density ratios of glassyto-crystalline forms in As 2 S 3 and SiO 2 implies that As 2 S 3 can expand since the glass is as dense as its crystal. When As 2 S 3 is exposed to illumination, the photoexpansion appears ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(59 citation statements)
references
References 38 publications
7
50
0
2
Order By: Relevance
“…There are several computer simulations, the results of which may be applicable to these excitations [32]. Interestingly, the bandgap excitations provide volume contraction (-ΔV), i.e., densification, in SiO 2 and expansion (+ΔV) in As 2 S 3, which seems to be related with open and dense glass structures [33]. Third, for sub-gap excitations (Fig.…”
Section: Nonlinear Optical Excitationmentioning
confidence: 99%
“…There are several computer simulations, the results of which may be applicable to these excitations [32]. Interestingly, the bandgap excitations provide volume contraction (-ΔV), i.e., densification, in SiO 2 and expansion (+ΔV) in As 2 S 3, which seems to be related with open and dense glass structures [33]. Third, for sub-gap excitations (Fig.…”
Section: Nonlinear Optical Excitationmentioning
confidence: 99%
“…It has been reported that the polyacrylamide network exhibits an inhomogeneous cross-link distribution [23]. Partially hydrolysed polyacrylamide gels experience volumetric phase transitions when changing the temperature, pH, and solvent composition [24]. Polyacrylamide gels are extensively used as matrix for electrophoresis, and to encapsulate drugs, enzymes and proteins for application in drug delivery systems and biosensors [25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Халькогенидные стекла представляют собой еще один класс светочувствительных материалов с зависящим от освещения объе-мом [3]. В неорганических сегнетоэлектрических кристаллах, таких как (Pb,La)(Zr,Ti)O 3 [4] и BiFeO 3 (BFO) [5], также наблюдалось фо-тоиндуцированное изменение размера, обусловленное фотострикцией.…”
Section: поступило в редакцию 20 ноября 2017 г в окончательной редакunclassified